2011
DOI: 10.1143/jjap.50.04da13
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Effects on Ge/SiO2 Interface Structure in Wafer-Bonded Germanium-on-Insulator Substrates

Abstract: We consider a field theory with target space being the two dimensional sphere S 2 and defined on the space-time S 3 × R. The Lagrangean is the square of the pullback of the area form on S 2 . It is invariant under the conformal group SO(4, 2) and the infinite dimensional group of area preserving diffeomorphisms of S 2 . We construct an infinite number of exact soliton solutions with non-trivial Hopf topological charges. The solutions spin with a frequency which is bounded above by a quantity proportional to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
4
7
0
Order By: Relevance
“…A smooth morphology was observed at the interface after annealing at 400qC, which was similar to the case after the 300qC preliminary annealing (6). On the other hand, nanometer-sized mound-like objects were frequently seen at the interfaces after annealing at 500700qC, as indicated by the arrows in Figs.…”
Section: Atomic and Chemical Structures Of Ge/box Interfaces In Goi Ssupporting
confidence: 68%
See 1 more Smart Citation
“…A smooth morphology was observed at the interface after annealing at 400qC, which was similar to the case after the 300qC preliminary annealing (6). On the other hand, nanometer-sized mound-like objects were frequently seen at the interfaces after annealing at 500700qC, as indicated by the arrows in Figs.…”
Section: Atomic and Chemical Structures Of Ge/box Interfaces In Goi Ssupporting
confidence: 68%
“…The presence of insulators improves the performance of MOSFETs due to the reduction of parasitic capacitance and enables an electrostatic control which is indispensable when downscaling the MOSFET dimensions. There are several methods for fabricating GOI substrates, such as wafer bonding (1)(2)(3)(4)(5)(6)(7)(8), Ge condensation (9)(10)(11), liquid-phase epitaxy (12,13), and separation by implanting oxygen (14,15). Among these methods, a wafer bonding technique using both Si wafers covered with SiO 2 layers and Ge wafers has an advantage that high crystalline quality of Ge layer is potentially accomplished, comparable to that of bulk Ge crystal.…”
Section: Introductionmentioning
confidence: 99%
“…1. Finally, the bonded wafers were annealed in N 2 atmosphere to further strengthen the bonding of the Ge/SiO 2 interface [6]. The resultant GOI substrate consisted of a sandwich structure with a top p-type Ge layer (GOI layer), buried oxide (BOX) layer, and p-type Si substrate.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates a reduction in the density of interface defect states and fixed charges. Unlike the annealing effect in vacuum in our previous paper , this improvement by post‐annealing is presumably because oxygen vacancies causing oxygen deficiency near the Ge/SiO 2 interfaces introduced in the wafer‐bonding process are diminished by the oxygen supply.…”
Section: Introductionmentioning
confidence: 64%
“…Furthermore, GeOI can be applied to the pseudo-MOSFET method, which allows for easy measurement of electrical properties [17][18][19][20] without many processes necessary for the transistor fabrication. In our previous studies [21,22], we fabricated non-doped Ge(001)-OI substrates and confirmed transistor operation using the pseudo-MOSFET method. The threshold voltage shift from the ideal threshold voltage and hysteresis was observed in the channel conductance versus gate voltage curves.…”
mentioning
confidence: 89%